1998
DOI: 10.1152/ajpendo.1998.274.1.e1
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelins in regulation of vascular tone in the in situ perfused rat adrenals

Abstract: This study examined the role of endothelins (ETs) and their receptor subtypes ETAand ETB in the regulation of vascular tone in the in situ perfused rat left adrenal gland. Endothelin-1 (ET-1), which binds both ETA and ETB receptors, decreased adrenal flow rate of the perfusion medium, and its effect was reversed by the ETA antagonist BQ-123 and enhanced by the ETB antagonist BQ-788. ET-3, which preferentially binds ETB, and the selective ETB agonist BQ-3020 increased adrenal flow rate of perfusate, and their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
2
10
1
Order By: Relevance
“…Endothelin was released in response to an increase in perfusion flow rate, while exogenous administration of ET caused a decrease in vascular perfusion. 12 In a similar study, Mazzocchi et al 49 showed that ET infusion causes a decrease in flow rate of the perfusion medium. Using specific antagonists for ET A and ET B receptors, they demonstrated that the decrease in flow rate was a result of ET A receptor activation, which required protein kinase C activation.…”
Section: Mechanisms By Which Et May Affect Adrenal Functionmentioning
confidence: 86%
“…Endothelin was released in response to an increase in perfusion flow rate, while exogenous administration of ET caused a decrease in vascular perfusion. 12 In a similar study, Mazzocchi et al 49 showed that ET infusion causes a decrease in flow rate of the perfusion medium. Using specific antagonists for ET A and ET B receptors, they demonstrated that the decrease in flow rate was a result of ET A receptor activation, which required protein kinase C activation.…”
Section: Mechanisms By Which Et May Affect Adrenal Functionmentioning
confidence: 86%
“…Thus, ET stimulates cortisol and aldosterone secretion directly and by enhancing ACTH action. Together with nitric oxide (NO) it regulates the adrenal vascular tone and stimulates adrenal growth (7,8). It was demonstrated that glucocorticosteroids induce ET release by vascular smooth muscle cells, suppress the activity of the NO system and thus cause vasoconstriction, endothelial dysfunction and atherosclerosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…In effect, ETs regulate vascular tone in in situ perfused rat adrenal gland, via both protein kinase C-coupled ET A and NOS-ET B receptors, whose activation evokes vasoconstriction and vasodilation, respectively (Mazzocchi et al, 1998). Probably, ET-induced activation of ET B receptors is modulated by endothelium-derived nitric oxide.…”
Section: Discussionmentioning
confidence: 98%